Exploration of the Independent Curriculum: Information Technology Collaboration in Multidisciplinary Learning in Situbondo Regency Elementary Schools - Dodik Eko Yulianto; Vidya Pratiwi; Reky Lidyawati; Afif Amroellah (STAI Hubbulwathan Duri, 2024)
Curricula serve as structured learning guides, framing students' educational journeys from inception to completion. In response to evolving science and technology, curricula must adapt to maintain engagement and relevance. This study investigates challenges in implementing independent curricula, particularly the preparedness of teachers to adopt innovative teaching approaches. A qualitative descriptive approach was utilized, emphasizing detailed narratives over numerical data. Data were collected through direct observations, interviews, and documentation. The analysis followed Miles and Huberman's framework, encompassing data reduction, data presentation, and conclusion drawing. Findings revealed that the primary challenge in implementing an independent curriculum lies in ensuring teachers possess the necessary competencies and support. Effective implementation requires training in interactive teaching methodologies, a thorough understanding of curriculum applications, and the ability to assess student achievements comprehensively. The study highlights a critical need for capacity building among educators to bridge the gap between curriculum design and classroom application. Addressing these challenges involves targeted teacher training programs, resource allocation, and consistent institutional support to facilitate a seamless transition. The successful implementation of independent curricula hinges on equipping teachers with the required skills and resources. Future efforts should focus on developing professional development frameworks to ensure sustainable and effective curriculum adaptation.